2000
DOI: 10.1128/aac.44.4.985-990.2000
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Intrapulmonary Pharmacokinetics of Rifapentine in Normal Subjects

Abstract: The intrapulmonary pharmacokinetics of rifapentine were studied in 30 volunteers who received a single, oral dose of rifapentine (600 mg). Subgroups of five subjects each underwent bronchoscopy and bronchoalveolar lavage (BAL) at timed intervals following drug administration. Drug concentrations, including the concentration of the primary metabolite 25-desacetyl rifapentine, were determined in plasma, BAL fluid, and alveolar cells (AC) by high-pressure liquid chromatography. The concentrations in epithelial li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…Researchers (1)(2)(3)(4)(5)(8)(9)(10)(11)(12)(13) have developed techniques for the measurement, in vivo, of the concentrations of drugs in ELF and AC. The purpose of this study was to determine the steady-state intrapulmonary concentrations and intrapulmonary pharmacokinetic parameters of orally administered linezolid in healthy volunteers.…”
mentioning
confidence: 99%
“…Researchers (1)(2)(3)(4)(5)(8)(9)(10)(11)(12)(13) have developed techniques for the measurement, in vivo, of the concentrations of drugs in ELF and AC. The purpose of this study was to determine the steady-state intrapulmonary concentrations and intrapulmonary pharmacokinetic parameters of orally administered linezolid in healthy volunteers.…”
mentioning
confidence: 99%
“…The EID or ODD concept of antibiotics has been widely accepted according to the results of intensive studies on pharmacokinetic characteristics of antibiotics (2,10,16,17). ODD uses an increased dose for the daily shot and is reported to have an improved efficacy due to concentration-dependent bactericidal activity and also is suggested to minimize the likelihood of developing toxicities comparing to the traditional multiple daily dosing (1,14).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the Cmax, Tmax values in plasma derived from this study were very similar to those reported in earlier studies with previous reports. (19)(20)(21). These data confirm that the high peak concentration of moxifloxacin also appears to result in a high intrapulmonary concentration, i.e., 2651.86 ± 560.42 mg/mL in AMs and 502.07 ± 131.99 mg/mL in ELF.…”
Section: Estimation Of Epithelial Lining Fluid (Elf) Volumes and Detementioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] The volume of ELF contained in each BALf sample was determined by the urea dilution method. Urea diffuses freely throughout the body with the concentration in plasma equal to that in other body fluids.…”
Section: Estimation Of Epithelial Lining Fluid (Elf) Volumes and Detementioning
confidence: 99%
See 1 more Smart Citation